1972
DOI: 10.1577/1548-8659(1972)34[222:eodoot]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dissolved Oxygen on Two Life Stages of the Mummichog

Abstract: THE NEED TO STUDY THE VARIOUS LIFE STAGES of marine animals in order to establish meaningful water quality standards has been stressed [8]. The mummichog (Fundulus heteroclitus) is common in tidal creeks and estuaries and is therefore subject to fluctuations in environmental parameters. There is no information available to describe the relative sensitivities of 1971. Standard methods for the examination of water and wastewater. 13th edition. New

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…No mortality was noted at DO concentrations ‡2.2 mg kg -1 . It was concluded that successful embryonic development of this species required higher DO concentrations than those required by adult individuals (Voyer and Hennekey 1972), with values for adults somewhat higher in that study than those of Smith and Able (2003), discussed earlier.…”
Section: Do Requirements For Development and Hatchingmentioning
confidence: 52%
See 1 more Smart Citation
“…No mortality was noted at DO concentrations ‡2.2 mg kg -1 . It was concluded that successful embryonic development of this species required higher DO concentrations than those required by adult individuals (Voyer and Hennekey 1972), with values for adults somewhat higher in that study than those of Smith and Able (2003), discussed earlier.…”
Section: Do Requirements For Development and Hatchingmentioning
confidence: 52%
“…These DO levels appear adequate for adult individuals of estuarine cyprinodontoids, with the exception of F. carpio (not present in the Virginia area), which would be stressed at even the highest levels recommended here (Kaill 1967). However, the lower limit of 2.3 mg/l, is lower than those considered adequate for development of eggs of F. heteroclitus (Voyer and Hennekey 1972;Taylor and DiMichele 1983).…”
Section: Do Standards For Marine Animalsmentioning
confidence: 78%
“…Bigelow & Schroeder (1953), Pickford et al (1969) and Voyer & Hennekey (1972) Etheostoma olmstedi (Percidae) and Anguilla rostrata (Anguillidae), also considered tolerant species. Prior to this study, the mummichog was recorded in the Bronx River (W. R. Whitworth, pers.…”
Section: Resultsmentioning
confidence: 99%
“…It may delay hatching (Voyer and Hennecky 1972), stimulate hatching (DiMichele and Powers 1984), reduce hatching success or induce deformities (Shumway et al 1964). Hypoxia can reduce larval growth rate (Rombough 1988), leading to protracted exposure to predators (Giorgi 1981).…”
Section: Tolerancementioning
confidence: 99%